Metal‐Free Multi‐Component Sulfur Dioxide Insertion Reaction Leading to Quinoxalin‐2‐One‐Containing Vinyl Sulfones under Visible‐Light Photoredox Catalysis. Issue 22 (23rd September 2021) - Lv, Yufen; Luo, Jinyun; Lin, Muze; He, Lin; Yue, Huilan; Liu, Ruisheng; Wei, Wei
Abstract: A metal‐free multi‐component sulfur dioxide insertion reaction of alkynes, sodium metabisulfite, aryldiazonium, and quinoxalin‐2‐ones has been developed under visible‐light photoredox‐catalysis. This photocatalytic tandem reaction would be conducted at room temperature by using of Rhodamine 6G as organic photocatalyst and sodium metabisulfite as the SO2 surrogate. This protocol provides a synthetic strategy for the construction of various quinoxalin‐2‐one‐containing vinyl sulfones with favourable functional group tolerance, in which one C−C bond and two C−S bonds were constructed in one pot procedure. Abstract :